Best Practice Recommendations for Geriatric Dysphagia Management with 5 Ws and 1H - ŞEN YAVUZ, BETÜL (My University, 2022)
Background: Dysphagia is a geriatric syndrome. Changes in the whole body that occur with aging also affect swallowing functions and cause presbyphagia. This condition may progress to oropharyngeal and/or esophageal dysphagia in the presence of secondary causes that increase in incidence with aging. However, no study has been published that provides recommendations for use in clinical practice that addresses in detail all aspects of the management of dysphagia in geriatric individuals. This study aimed to answer almost all potential questions and problems in the management of geriatric dysphagia in clinical practice. Methods: A multidisciplinary team created this recommendation guide using the seven-step and three-round modified Delphi method via e-mail. The study included 39 experts from 29 centers in 14 cities. Results: Based on the 5W and 1H method, we developed 216 detailed recommendations for older adults from the perspective of different disciplines dealing with older people. Conclusion: This consensus-based recommendation is a useful guide to address practical clinical questions in the diagnosis, rehabilitation, and follow-up for the management of geriatric dysphagia and also contains detailed commentary on these issues.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Geriatri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Geriatrics; Health Sciences; GERİATRİK VE GERONTOLOJİ; Klinik Tıp; Klinik Tıp (MED); GERIATRICS & GERONTOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Geriatri ve Gerontoloji; Geriatrics and Gerontology; Oropharyngeal dysphagia; Esophageal dysphagia; Geriatrics; Consensus; Diagnosis; Rehabilitation